Assessment of [(3)H]Thymidine Incorporation into DNA as a Method To Determine Bacterial Productivity in Stream Bed Sediments - Kaplan, Louis A. (1992)
We performed several checks on the underlying assumptions and procedures of the thymidine technique applied to stream bed sediments. Bacterial production rates were not altered when sediments were mixed to form a slurry. Incubation temperature did affect production rates. Controls fixed and washed with formaldehyde had lower backgrounds than trichloroacetic acid controls. DNA extraction by base hydrolysis was incomplete and variable at 25°C, but hydrolysis at 120°C extracted 100% of the DNA, of which 84% was recovered upon precipitation. Production rates increased as thymidine concentrations were increased over 3 orders of magnitude (30 nM to 53 μM thymidine). However, over narrower concentration ranges, thymidine incorporation into DNA was independent of thymidine concentration. Elevated exogenous thymidine concentrations did not eliminate de novo synthesis. Transport of thymidine into bacterial cells occurred at least 5 to 20 times faster than incorporation of label into DNA. We found good agreement between production rates of bacterial cultures based upon increases in cell numbers and estimates based upon thymidine incorporation and amount of DNA per cell. Those comparisons emphasized the importance of isotopic dilution measurements and validated the use of the reciprocal plot technique for estimating isotopic dilution. Nevertheless, the thymidine technique cannot be considered a routine assay and the inability to measure the cellular DNA content in benthic communities restricts the accuracy of the method in those habitats.